Organizational innovation for SME'S: a model for Latvia - Flores, Ricardo Martin; Apsalone, Madara; Baumane-Vitolina, Ilona; Sumilo, Erika (University of Latvia, 2020)
Small and medium-sized enterprises (SMEs) can be a significant source of innovation in small economies. SMEs face challenges of limited capacity, personnel and resources for long-term investments. Additionally, they might not see and understand the benefits of innovation. Implementation of organizational innovation (OI) could give such enterprises an opportunity to improve competitiveness and develop other types of innovation. The purpose of this study is to develop a model, explaining OI through such factors as organizational culture (OC) and knowledge management (KM) in SMEs via an empirical study across various industries. Surveying 600 SMEs in Latvia, the authors explore the contribution of organizational factors - cooperation, trust, inclusive decision making, result orientation and long-term strategic planning, as well as knowledge management and organizational learning processes to OI performance. The authors propose a conceptual model in several steps, the current step focuses on Organizational Innovation Analysis through Regression Methods and on a final step a whole model for all kinds of Innovation outputs (not only organizational) will be designed through Structural Equation Modelling. After current analysis the influence of Human/Individual values over Organizational Innovation seems to be confirmed.
Keywords: innovation; organizational innovation; organizational learning; regression models; organizational culture; Research Subject Categories::SOCIAL SCIENCES::Business and economics